Characterization, antioxidant and antibacterial activity of essential oils and their encapsulation into biodegradable material followed by freeze drying - Kokina, Mariia (Array, 2019)
The study assessed the antimicrobial and antioxidant activities of commonly used and commercially available essential oils as an alternative to synthetic preservatives. The plant sources were as follows: lavender (Lavandula angustifolia), tea tree (Melaleuca alternifolia), bergamot (Citrus bergamia) and peppermint (Mentha piperita). The antioxidant activity of essential oils was tested by the 2,2-diphenyl-1-picrylhydrazyl (DPPH) and 2,2´-azinobis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) methods. The microdilution broth susceptibility assay revealed that lavender and bergamot essential oils were more efficient in inhibiting the bacterial growth than other tested oils, with the minimum inhibitory concentration of 5 μg/mL. This study also reports the successful implementation of an electrostatic extrusion technique for encapsulating essential oils into alginate beads, which enables the essential oils to maintain their free radical scavenging ability over time.